STRATEGI PENCEGAHAN PERNIKAHAN DINI MELALAUI PENDIDIKAN AGAMA ISLAM: Pernikahan dini,pendidikan Agama islam, Remaja, Pencegahan - St. Nurul Isnah Umayana; Sulfikar Muhaemin; Tiara Rezkika Andini; Rabiatul adawiah; Amirul Haq (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
Early marriage is a social problem that still frequently occurs in Indonesia and causes various negative impacts on health, psychological well-being, education, and social life. This phenomenon is generally influenced by low educational levels, economic conditions, cultural factors, and a lack of understanding of Islamic teachings that emphasize physical and mental readiness for marriage. Islamic Religious Education plays a strategic role in shaping the moral and spiritual awareness of adolescents so that they are able to make wise decisions regarding marriage. This study aims to analyze the role of Islamic Religious Education in preventing early marriage, identify prevention strategies implemented through Islamic Religious Education, and examine the supporting and inhibiting factors in its application. This research employs a library research method with a qualitative descriptive approach by analyzing books, scientific journals, and relevant documents. The findings indicate that Islamic Religious Education is essential in instilling values of responsibility, patience, self-control, and understanding the purpose and responsibilities of marriage in Islam. Therefore, strengthening Islamic Religious Education through formal, non-formal, and informal channels can serve as an effective effort to prevent early marriage and to develop a faithful, moral, and responsible young generation.